"So Can She Cook?" The Activity Process beyond a Narrative of Function. Issue 4 (1st October 2016) - Michael, Lorraine
Abstract: This article is about the meaning of the activity process beyond the purpose of function, performance, and outcome. Expounding on the seminal work of psychoanalytic occupational therapists who posit a symbolic, relational, and transformative view of activity, the author positions a response to a typical question relating to the activity process that continues to arise within multidisciplinary discussions. Drawing on her clinical work as an allied health clinician in acute psychiatry, she sheds light on how the above lens can deepen the understanding of "doing" to provide clinicians with crucial insights into a client's inner world and the dynamics of the therapeutic relationship. She illustrates this through the use of a vignette. She concludes by discussing the implications of reframing the activity process beyond "function" for our work with clients.